Safety assessment of a novel water-soluble extract of Boswellia serrata gum resin: acute toxicity, 90-day sub-chronic toxicity, Ames' bacterial reverse mutation, and in vivo micronucleus assays. (13th June 2022) - Dodda, Sundararaju; Madireddy, Ravi Kumar; Alluri, Venkata Krishnaraju; Golakoti, Trimurtulu; Sengupta, Krishanu
Abstract: Boswellia serrata gum resin extracts have demonstrated potential benefits in alleviating joint pain and discomfort of osteoarthritis. The major objective of the present study was to assess the safety of a water-soluble B. serrata gum resin extract (LI51202F1) in diverse models of acute oral, acute dermal, primary dermal irritation, eye irritation, and 90-day sub-chronic repeated dose toxicity studies, as well as Ames' bacterial reverse mutation assay and in vivo micronucleus assay. The acute oral and dermal toxicity studies in Sprague Dawley (SD) rats demonstrated that the median lethal dose (LD50 ) of LI51202F1 is >2000 mg/kg body weight (BW). The acute dermal and eye irritation tests in New Zealand white rabbits exhibited that LI51202F1 is non-irritating to the skin and mildly irritating to the eyes, respectively. The 90-days sub-chronic repeated oral dose study demonstrated that the LI51202F1-treated male and female SD rats did not show signs of toxicity on their BW, food intake, organ weights, thyroid hormones, and on the clinical pathology, gross pathology, and histopathological assessments. In male and female rats, the no-observed-adverse-effect level (NOAEL) of LI51202F1 was 500 mg/kg/day, the highest tested dose in the study. The results of the bacterial reverse mutation assay in Salmonella typhimurium TA98, TA100, TA1535, TA1537, and Escherichia coli WP2uvrA (pKM101) strains in the presence or absence of S9 metabolic activation system and a micro-nucleus assay in mouse bone marrow erythrocytes demonstrated that LI51202F1 is neither mutagenic nor clastogenic. In conclusion, under the conditions of these studies, LI51202F1 demonstrated broad-spectrum safety.